Pengaruh Minat Membaca Terhadap Keterampilan Berbicara Siswa Tingkat Sekolah Dasar (SD): A Literature Review - Vipassana, Vania; Dadi Satria (Asosiasi Periset Bahasa Sastra Indonesia, 2026)
This study aims to examine the relationship between reading interest and students' speaking skills at the elementary school level using a literature review approach. The background of this study focuses on the importance of reading interest as an element of speaking skills that need to be honed from an early age, and there is a strong assumption that reading interest has a major influence in improving these skills. The method applied is an analysis of five scientific articles found through a search using the keywords